Sustainable development goals: is the global framework for fighting financial crime aligned with environmental objectives? - Feridun, Mete (Routledge Journals, Taylor & Francis Ltd, 2024)
This article explores the impact of anti-money laundering and countering the financing of terrorism (AML/CFT) regulations on environmental performance for a sample of 141 countries. Results of cross-sectional regression models show that the impact is significant and negative, which suggests that the current AML/CFT regulations jeopardize global efforts towards achieving the United Nation's Sustainable Development Goals by 2030 as planned. This can be attributed to the costly efforts of compliance with AML/CFT regulations which may be holding back the finance sector from prioritizing environmental goals.
Keywords: SDGs; environmental performance; financial crime; AML/CFT